Comparison of physiochemical attributes, microbial community, and flavor profile of beef aged at different temperatures - Yu, Haojie; Zhang, Songshan; Liu, Xiaochang; Lei, Yuanhua; Wei, Meng; Liu, Yinchu; Yang, Xiaodong; Xie, Peng; Sun, Baozhong (Frontiers in Microbiology, 2022)
This study aims to decrease aging time by increasing temperature. Beef were aged and vacuum packaged at 10 °C and 15 °C, and the effects of increased temperature on meat physiochemical attributes, microbial community, and flavor profile were monitored. The shear force decreased with aging in all temperature and showed the higher rate at elevated temperatures compare to 4 °C. The beef aged at elevated temperatures (10 °C or 15 °C) for 5 days showed equivalent shear force value to the beef aged at 4 °C for 10 days (P > 0.05), however, the final tenderness was not affected by the elevated temperature. The beef aged at elevated temperatures showed a significantly higher cooking loss and less color stability compared to 4 °C (P < 0.05). The total volatile basic nitrogen and aerobic plate count increased (P < 0.05) faster at elevated temperatures compare to 4 °C. Carnobacterium, Lactobacillus and Hafnia–Obesumbacterium were the dominant genus in the beef samples aged at 4 ℃, 10 ℃, and 15 ℃, respectively. In addition, the contents of isobutyraldehyde, 3-methylbutyraldehyde, 2-methylbutyraldehyde, and 3-methylbutanol were higher than aged at 4 °C (P < 0.05). Therefore, these results suggest that application of elevated aged temperatures could shorten required aging time prior while not adversely affecting meat quality.